Holocaust, genocide, and the law: a quest for justice in a post-Holocaust world - Bazyler, Michael J. (Oxford University Press, 2016)
The holocaust : a legal history -- Naming the crime : genocide -- Prosecution of Nazi war criminals at Nuremberg -- National prosecutions of Nazi war criminals -- Civil litigation for the financial crimes of the holocaust -- Holocaust denial and the law -- The impact of the holocaust on post-holocaust legal philosophy -- Nuremberg's legacy : the UN Tribunals for Yugoslavia and Rwanda and the International Criminal Court -- Prosecuting genocide